2014
DOI: 10.2105/ajph.2014.302099
|View full text |Cite
|
Sign up to set email alerts
|

Community Socioeconomic Disadvantage and the Survival of Infants With Congenital Heart Defects

Abstract: Objectives We examined the association between survival of infants with severe congenital heart defects (CHDs) and community-level indicators of socioeconomic status. Methods We identified infants born to residents of Arizona, New Jersey, New York, and Texas between 1999 and 2007 with selected CHDs from 4 population-based, statewide birth defect surveillance programs. We linked data to the 2000 US Census to obtain 11 census tract–level socioeconomic indicators. We estimated survival probabilities and hazard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 55 publications
1
61
1
1
Order By: Relevance
“…Additional limitations include: (1) wide 95% CIs associated with the estimated survival probabilities for several defects among A/PI and AI/AN subgroups attributable to small sample sizes; and (2) lack of data on potentially important clinical factors (eg, timing and age of the child at initial diagnosis, the severity of the defect, and whether the child had isolated or nonisolated defects), demographic factors (eg, socioeconomic status 13 and health insurance payer 29 ) and hospital factors (eg, nursery care level at the hospital of delivery 35 ) that are also likely to play a role. Considering these limitations and the descriptive nature of the analysis, the survival estimates presented here should be interpreted cautiously.…”
Section: Discussionmentioning
confidence: 99%
“…Additional limitations include: (1) wide 95% CIs associated with the estimated survival probabilities for several defects among A/PI and AI/AN subgroups attributable to small sample sizes; and (2) lack of data on potentially important clinical factors (eg, timing and age of the child at initial diagnosis, the severity of the defect, and whether the child had isolated or nonisolated defects), demographic factors (eg, socioeconomic status 13 and health insurance payer 29 ) and hospital factors (eg, nursery care level at the hospital of delivery 35 ) that are also likely to play a role. Considering these limitations and the descriptive nature of the analysis, the survival estimates presented here should be interpreted cautiously.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, societal factors such as poverty, medical insurance, and maternal education have emerged as predictors of adverse outcomes in children with complex congenital heart disease (CHD) and may explain some of the difference in survival between children with similar clinical characteristics 9. Specifically, low socioeconomic status (SES) in children with SV physiology has been associated with higher early mortality6, 8 and lower quality of life10 after surgery, and other studies have found similar associations in the larger CHD population 11, 12, 13, 14, 15, 16. Nevertheless, existing studies examining SES have been limited by cross‐sectional or case–control study designs,14, 15 single center populations,7, 9, 10, 14, 15 or limited outcome assessment 6, 8.…”
Section: Introductionmentioning
confidence: 99%
“…Andersen et al showed that children from lower‐income neighborhoods have worse mortality and higher resource utilization, including LOS and hospital costs, after cardiac surgery. Similarly, Kucik et al demonstrated an increased mortality in infants with CHD from socioeconomically disadvantaged communities. Among OHT patients, Singh and colleagues showed that low SES is associated with greater risk of rejection and OHT graft loss .…”
Section: Discussionmentioning
confidence: 89%